A low-temperature sintering silver paste with high sintering activity and preparation method thereof
By replacing nano-silver-coated low-temperature glass powder with nano-silver coating, the problems of high cost and poor conductivity of low-temperature sintered silver paste are solved, the formation of high-density silver layer and the reliability of the device are achieved, and the volume resistivity and Contact resistance.
Patent Information
- Application Number
- CN202411122876.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-08-15
- Publication Date
- 2024-12-17
- Estimated Expiration
- 2044-08-15
AI Technical Summary
The existing low-temperature sintered silver paste requires the use of expensive nano silver powder, which leads to high cost and poor conductivity.
Conductive low-temperature glass powder is used to replace nano-silver powder. The low-temperature glass powder coated by nano-silver is melted at low temperatures, promoting the tight bonding of micron or sub-micron silver powder, forming a high-density silver layer, reducing volume resistivity, and passing through reasonable glass Powder component design improves the adhesion and durability of the device.
It significantly reduces the cost of low-temperature sintered silver paste, improves the conductivity and density of the silver layer, meets the needs of high adhesion, acid and alkali resistance, high temperature resistance, low temperature resistance and aging resistance of the device, and reduces the volume resistivity and Contact resistance.
Smart Images

Figure CN118658656B_ABST
Abstract
Description
Technical Field
[0001] The present application belongs to the technical field of silver paste, and in particular relates to a low-temperature sintering silver paste with high sintering activity and a preparation method thereof. Background Art
[0002] Low-temperature sintering silver paste is widely used in the fields of solar cells and semiconductor packaging because of its low sintering temperature and little damage to materials. It is generally composed of curing resin, curing agent, nano silver powder, micron or submicron silver powder, solvent and functional additives. Among them, nano silver powder is used to melt and connect micron or submicron silver powder during low-temperature sintering to form a good conductive network, thereby meeting the functional requirements of the silver layer. This requires that the nano silver powder has good particle size uniformity, small enough particle size and high enough low-temperature sintering activity, but its preparation process is relatively complicated and requires high technical level, resulting in the high price of nano silver powder, which is much higher than the price of conventional micron or submicron silver powder. If nano silver powder is used less or not in order to control the cost of low-temperature sintering silver paste, insufficient low-temperature sintering is likely to occur, and micron or submicron silver powder cannot be effectively fused, resulting in the problem of poor conductivity of the silver layer after low-temperature sintering and curing. If in order to make micron or submicron silver powder effectively fuse and meet the conductivity requirements, more nano silver powder is required, which will undoubtedly increase the cost of silver paste, and at the same time increase the viscosity of silver paste and increase the difficulty of uniform coating. Therefore, it is of great significance to develop a feasible solution to replace expensive nano-silver powder. Summary of the invention
[0003] The purpose of the present application is to provide a low-temperature sintering silver paste with high sintering activity and a preparation method thereof, aiming to solve the problem that the existing low-temperature sintering silver paste requires the use of nano silver powder, resulting in excessively high costs.
[0004] In order to achieve the above application purpose, the technical solution adopted in this application is as follows:
[0005] In a first aspect, the present application provides a low-temperature sintering silver paste with high sintering activity, comprising the following components in weight proportions: 40 to 95 parts of micron or submicron silver powder, 0.5 to 10 parts of conductive low-temperature glass powder, 0.5 to 10 parts of resin, 0.1 to 5 parts of curing agent, 3 to 50 parts of solvent, and 0 to 10 parts of additives.
[0006] In a second aspect, the present application provides a method for preparing a low-temperature sintering silver paste, characterized in that it comprises the following steps:
[0007] Weigh micron or submicron silver powder, conductive low-temperature glass powder, resin, curing agent, solvent and additives;
[0008] Dispersing the resin and the curing agent in the solvent to obtain a dispersion;
[0009] The micron or submicron silver powder, the conductive low-temperature glass powder and the additive are added into the dispersion and mixed evenly to obtain a low-temperature sintering silver paste.
[0010] Compared with the prior art, this application has the following beneficial effects:
[0011] The low-temperature sintering silver paste with high sintering activity provided in the first aspect of the present application contains a conductive low-temperature glass powder with a very low glass transition temperature (Tg), a very high low-temperature sintering activity and good sintering shrinkage characteristics, which can achieve good leveling and wetting characteristics at a lower temperature, promote the melting of micron or submicron silver powder in the silver paste, make the micron or submicron silver powder tightly combined and shrink the volume, improve the compactness of the silver layer after the silver paste is sintered at low temperature, and greatly reduce the volume resistivity of the silver layer. Therefore, low-temperature sintering can be achieved and good conductivity can be formed to meet the application requirements of the device. At the same time, compared with the pure resin organic bonding phase, the added conductive low-temperature glass powder can also be used as an inorganic bonding phase. Therefore, through a reasonable design of the glass powder component, the crystallinity of the glass powder before and after sintering can be improved, and the reliability requirements of the device such as high adhesion, acid and alkali resistance, high temperature resistance, low temperature resistance, and aging resistance can be achieved. In addition, the use of conductive low-temperature glass powder can also greatly reduce the amount of resin used and broaden the range of resin selection, so as to further improve the conductivity of the silver layer. Therefore, the present application utilizes conductive low-temperature glass powder to replace nano silver powder, thereby reducing the volume resistivity and contact resistance of the silver layer and significantly reducing the cost of low-temperature sintering silver paste.
[0012] The second aspect of the present application provides a method for preparing a low-temperature sintering silver paste with high sintering activity. The method first disperses a resin and a curing agent in a solvent to form a dispersion, and then adds micron or submicron silver powder, conductive low-temperature glass powder and additives to the dispersion and mixes them evenly to obtain a low-temperature sintering silver paste. Therefore, the preparation process is simple, easy to operate and low-cost. BRIEF DESCRIPTION OF THE DRAWINGS
[0013] In order to more clearly illustrate the technical solutions in the embodiments of the present application, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present application. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying any creative work.
[0014] Figure 1 This is a SEM image of the contact layer in the electrode formed by printing the low-temperature sintered silver paste provided in Example 1 of the present application. DETAILED DESCRIPTION
[0015] In order to make the technical problems, technical solutions and beneficial effects to be solved by the present application more clearly understood, the present application is further described in detail below in conjunction with the embodiments. It should be understood that the specific embodiments described herein are only used to explain the present application and are not used to limit the present application.
[0016] The first aspect of an embodiment of the present application provides a low-temperature sintering silver paste with high sintering activity, comprising the following components in parts by weight: 40 to 95 parts of micron or submicron silver powder, 0.5 to 10 parts of conductive low-temperature glass powder, 0.5 to 10 parts of resin, 0.1 to 5 parts of curing agent, 3 to 50 parts of solvent, and 0 to 10 parts of additives.
[0017] The low-temperature sintering silver paste with high sintering activity provided in the embodiment of the present application contains a conductive low-temperature glass powder with a very low glass transition temperature (Tg), a very high low-temperature sintering activity and good sintering shrinkage characteristics, which can achieve good leveling and wetting characteristics at a relatively low temperature, promote the melting of micron or submicron silver powder in the silver paste, make the micron or submicron silver powder tightly combined and shrink the volume, improve the compactness of the silver layer after the silver paste is sintered at low temperature, and reduce the volume resistivity of the silver layer, so that low-temperature sintering can be achieved and good conductivity can be formed to meet the application requirements of the device. At the same time, compared with the pure resin organic bonding phase, the added conductive low-temperature glass powder can also be used as an inorganic bonding phase, so through a reasonable glass powder component design, the crystallinity of the glass powder before and after sintering can be improved, and the reliability requirements of the device such as high adhesion, acid and alkali resistance, high temperature resistance, low temperature resistance, and aging resistance can be achieved. In addition, the use of conductive low-temperature glass powder can also greatly reduce the amount of resin used and broaden the range of resin selection, so as to further improve the conductivity level of the silver layer. Therefore, the present application utilizes conductive low-temperature glass powder to replace nano silver powder, thereby reducing the volume resistivity and contact resistance of the silver layer and significantly reducing the cost of low-temperature sintering silver paste.
[0018] In an embodiment, the conductive low-temperature glass powder is a nano-silver coated low-temperature glass powder; based on the total weight of the low-temperature glass powder as 100%, the nano-silver coated low-temperature glass powder includes: Ag 1~10%, P2O55~60%, CaSO45~20%, TeO210~50%, V2O55~50%, GeO20.2~10%, GaInSn 0.2~5%, Ga or In 0.2~5%. The nano silver coated on the surface of the low-temperature glass powder has good sintering shrinkage characteristics, which can promote the bonding between micron or submicron silver powders to form a tightly bonded grid electrode, thereby reducing the volume and volume resistivity; the P2O5, CaSO4, TeO2, V2O5 and GeO2 contained in the glass powder give the glass powder a lower melting temperature and better stability; Ga or In single metal as an ultra-low melting point element further reduces the melting temperature of the glass powder, allowing the glass powder to melt and flow at a lower temperature, making the micron or submicron silver powder more tightly bonded, so that after the silver paste is sintered at low temperature, the silver layer has a better density and a lower volume resistivity. ;GaInSn alloy as a promoter has an ultra-low melting point and can be fused with TCO (transparent conductive oxide) layer elements, so that the glass powder can infiltrate the TCO layer material and flow in the TCO layer; therefore, the nanosilver-coated low-temperature glass powder in the low-temperature sintering silver paste contains these components and can melt below 220°C. The conductive low-temperature glass powder can penetrate the TCO layer at low temperatures, so that the nanosilver melted in the low-temperature glass powder will regenerate nanosilver at the interface between the TCO layer and the silicon layer after solidification to form an ohmic contact with the silicon layer, thereby reducing the contact resistance in the heterojunction solar cell and improving the photoelectric conversion efficiency of the photovoltaic cell. In addition, the use of nanosilver-coated low-temperature glass powder to replace nanosilver powder can significantly reduce the cost of low-temperature sintering silver paste. At the same time, the use of nanosilver-coated low-temperature glass powder can also reduce the use of resin, thereby improving the conductivity of the silver layer, and can also serve as an inorganic bonding phase, which helps to improve the density and adhesion of the silver layer after the silver paste is solidified, so that the resistance is significantly reduced.
[0019] In the embodiment, the D50 particle size of the low-temperature glass powder is 100~500nm, preferably 100~300nm. The low-temperature glass powder in this particle size range not only has high sintering activity, so that the low-temperature sintered silver paste can be solidified and formed at a lower sintering temperature, but also melts first and wets and wraps the silver particles as a binding phase, promoting micron or submicron dispersion and rearrangement, thereby forming a denser conductive network and reducing the volume resistivity of the silver layer after the silver paste is solidified.
[0020] In an embodiment, the D50 particle size of the nano-silver coated low-temperature glass powder is 150-600 nm, preferably 150-350 nm.
[0021] In an embodiment, the glass transition temperature of the low-temperature glass powder is 120~220°C, preferably 150~200°C. This glass transition temperature range enables the low-temperature glass powder to have high low-temperature sintering activity and good leveling and wetting properties, and can promote the melting of micron or submicron silver powder in the silver paste, improve the density of the silver layer after the silver paste is sintered and solidified, and reduce the volume resistivity.
[0022] In the embodiment, the D50 particle size of the micron or submicron silver powder is 0.5-10 μm. The micron or submicron silver powder in this particle size range is easier to disperse evenly in the silver paste, which helps to print and form a denser conductive network and lower volume resistivity.
[0023] In an embodiment, the micron or submicron silver powder includes any one of micron or submicron silver powder modified by polyvinyl pyrrolidone (PVP) and micron or submicron silver powder modified by oleic acid. By coating and modifying the micron or submicron silver powder with PVP or oleic acid, the dispersion effect of the micron or submicron and the coating uniformity of the silver paste can be improved.
[0024] In an embodiment, the resin is selected from at least one of epoxy resin, polyester resin, acrylic resin, ethyl cellulose, and polyvinyl butyral. Among them, the epoxy resin is selected from any one or more combinations of bisphenol A epoxy resin, bisphenol F epoxy resin, hydrogenated bisphenol A epoxy resin, hydrogenated bisphenol F epoxy resin, alicyclic epoxy resin, and bisphenol A diglycidyl ether; the polyester resin is selected from one or two combinations of saturated polyester resin and unsaturated polyester resin; the acrylic resin is selected from one or more combinations of thermoplastic acrylic resin, thermosetting acrylic resin, and self-crosslinking acrylic resin.
[0025] In an embodiment, the curing agent is selected from at least one of dicyandiamide, hexafluoroantimonate, methyltetrahydrophthalic anhydride, dodecenylsuccinic anhydride, polysebacic anhydride, and boron trinitride ethylamine complex.
[0026] In an embodiment, the solvent is selected from at least one of diethylene glycol butyl ether, diethylene glycol ethyl ether, diethylene glycol diethyl ether, diethylene glycol dibutyl ether, ethylene glycol phenyl ether, diethylene glycol ethyl ether acetate, diethylene glycol butyl ether acetate, DBE, dodecanol ester, hexadecanol ester, pineol, propylene glycol methyl ether acetate, 1-phenoxy-2-propanol, and diacetin.
[0027] In an embodiment, the low-temperature sintering silver paste may include the following components in parts by weight: 40 to 95 parts of micron or submicron silver powder, 0.5 to 10 parts of conductive low-temperature glass powder, 0.5 to 10 parts of resin, 0.1 to 5 parts of curing agent, 3 to 50 parts of solvent, and 1 to 10 parts of additives.
[0028] In an embodiment, the additives may include inorganic additives and organic additives; wherein the inorganic additives are selected from at least one of nano tin oxide powder, nano indium oxide powder, micron copper powder, and micron silver-coated copper powder; the organic additives are selected from at least one of dispersants, leveling agents, and thixotropic agents, specifically, the dispersant is selected from one or more of sodium dodecyl sulfate, sodium hexadecylbenzenesulfonate, hexadecyltrimethylammonium bromide, and polyvinylpyrrolidone; the leveling agent is selected from methyl acrylate; and the thixotropic agent is selected from silica with a particle size of 5 to 50 nm.
[0029] A second aspect of the embodiment of the present application provides a method for preparing a low-temperature sintering silver paste with high sintering activity, characterized in that it comprises the following steps:
[0030] S01: Weigh micron or submicron silver powder, conductive low-temperature glass powder, resin, curing agent, solvent and additives;
[0031] S02: dispersing the resin and the curing agent in a solvent to obtain a dispersion;
[0032] S03: adding micron or submicron silver powder, conductive low-temperature glass powder and additives into the dispersion and mixing them evenly to obtain low-temperature sintering silver paste.
[0033] The method for preparing a low-temperature sintering silver paste with high sintering activity provided in an embodiment of the present application is to first disperse a resin and a curing agent in a solvent to form a dispersion, and then add micron or submicron silver powder, conductive low-temperature glass powder and additives to the dispersion and mix them evenly to obtain a low-temperature sintering silver paste. Therefore, the preparation process is simple, easy to operate and low in cost.
[0034] In the above step S01, the step of preparing the conductive low-temperature glass powder includes: dissolving the silver source in a solvent, then adding the low-temperature glass powder and the reducing agent, performing a liquid phase reduction treatment, forming nanosilver on the surface of the low-temperature glass powder, and then filtering, washing and drying in sequence to obtain the conductive low-temperature glass powder. The molar ratio of the silver source to the second reducing agent is 1 / (1-4); the silver source is selected from at least one of silver nitrate, silver chloride, and silver acetate; the reducing agent is selected from at least one of hydrazine hydrate, ascorbic acid, and glucose; the pH value of the liquid phase reduction treatment is 8.5-9.5, the temperature is 50-100°C, and the time is 0.5-4h.
[0035] In an embodiment, the step of preparing low-temperature glass powder includes: weighing P2O5 powder, CaSO4 powder, TeO2 powder, V2O5 powder, GeO2 powder, GaInSn alloy liquid, Ga or In single substance; mixing P2O5 powder, CaSO4 powder, TeO2 powder, V2O5 powder and GeO2 powder, performing a first smelting treatment, and then quenching to obtain a first glass slag; performing a second smelting treatment on the first glass slag and GaInSn alloy liquid, Ga or In single substance under a protective atmosphere to obtain a second glass slag; sand-milling the second glass slag, and then sieving to obtain a low-temperature glass powder with a D50 particle size of 100 to 500 nm. The protective atmosphere can be nitrogen or argon. Oxide powders such as P2O5 and CaSO4 are preferentially melted and quenched once to reduce the melting temperature of the resulting glass slag, so as to facilitate secondary melting with GaInSn alloy liquid, Ga or In single substance at a lower temperature and in a protective atmosphere, thereby preventing the GaInSn alloy liquid, Ga or In single substance from being oxidized.
[0036] In the embodiment, the temperature of the first smelting treatment is 700-1500° C., and the time is 10-120 min; the temperature of the second smelting treatment is 200-300° C., and the time is 10-120 min.
[0037] The following describes the invention in conjunction with specific embodiments.
[0038] Example 1
[0039] This embodiment provides a low-temperature sintering silver paste with high sintering activity and a preparation method thereof.
[0040] The low-temperature sintering silver paste comprises: 70 parts of micron silver powder, 5 parts of nano-silver coated low-temperature glass powder, 5 parts of bisphenol A epoxy resin, 2.5 parts of dicyandiamide, and 25 parts of diethylene glycol butyl ether; wherein the nano-silver coated low-temperature glass powder comprises: Ag5%, P2O525%, CaSO415%, TeO225%, V2O520%, GeO25%, GaInSn 2.5%, and In 2.5%; the D50 particle size of the micron silver powder is 5μm, the D50 particle size of the low-temperature glass powder is 300nm, and the glass transition temperature is 202.7℃.
[0041] The method for preparing low-temperature sintering silver paste comprises the following steps:
[0042] S11: Preparation of Nanosilver-coated Low-temperature Glass Powder:
[0043] According to the formula of the nanosilver-coated low-temperature glass powder of Example 1, weigh appropriate amounts of P2O5 powder, CaSO4 powder, TeO2 powder, V2O5 powder, GeO2 powder, GaInSn alloy liquid, and In single substance powder;
[0044] P2O5 powder, CaSO4 powder, TeO2 powder, V2O5 powder and GeO2 powder are mixed and loaded into an alumina crucible, and then placed in a melting furnace and kept at 1200° C. for 60 minutes to form glass liquid; the glass liquid is poured into deionized water for quenching, and then dried and crushed to obtain a first glass slag;
[0045] The first glass slag, GaInSn alloy liquid and In elemental powder are placed in an alumina crucible, and then placed in an atmosphere furnace, nitrogen is introduced, and the temperature is kept at 230° C. for 60 minutes to form glass liquid; the glass liquid is poured into deionized water for quenching, and then dried and crushed to obtain the second glass slag;
[0046] The second glass slag is placed in a sand mill for sand grinding, and then sieved to obtain a low-temperature glass powder with a D50 particle size of 300 nm;
[0047] According to the molar ratio of silver nitrate to hydrazine hydrate (concentration of 80%) being 1 / 2, appropriate amounts of silver nitrate and hydrazine hydrate are weighed; silver nitrate is dissolved in water, and then low-temperature glass powder and hydrazine hydrate are added and mixed evenly, the pH is adjusted to 8.5, and the mixture is heated to 85°C for liquid phase reduction for 2 hours, and then filtered, washed and dried to obtain nano-silver coated low-temperature glass powder;
[0048] S12: weigh 70 parts of micron silver powder, 5 parts of nano silver-coated low-temperature glass powder, 5 parts of bisphenol A epoxy resin, 2.5 parts of dicyandiamide and 25 parts of diethylene glycol butyl ether;
[0049] S13: dispersing bisphenol A epoxy resin and dicyandiamide in diethylene glycol butyl ether to obtain a dispersion;
[0050] S14: adding micron silver powder and nano silver coated low temperature glass powder into the dispersion, mixing evenly, and then grinding to obtain low temperature sintering silver paste.
[0051] Example 2
[0052] This embodiment provides a low-temperature sintering silver paste with high sintering activity and a preparation method thereof, which is different from Embodiment 1 in that:
[0053] Low-temperature sintering silver paste, In in the low-temperature glass powder coated with nano-silver is replaced by Ga.
[0054] In the method for preparing low-temperature sintering silver paste, in step S11, the In elemental powder is replaced by a Ga ingot.
[0055] Example 3
[0056] This embodiment provides a low-temperature sintering silver paste with high sintering activity and a preparation method thereof, which is different from Embodiment 1 in that:
[0057] In the low-temperature sintering silver paste, the low-temperature glass powder coated with nanosilver includes: Ag 1%, P2O 56%, CaSO 4 20%, TeO 2 48%, V2O 5 10%, GeO 25%, GaInSn 5%, and In 5%; the D50 particle size of the low-temperature glass powder is 300nm and the glass transition temperature is 123.1°C.
[0058] Example 4
[0059] This embodiment provides a low-temperature sintering silver paste with high sintering activity and a preparation method thereof, which is different from Embodiment 1 in that:
[0060] In the low-temperature sintering silver paste, the low-temperature glass powder coated with nanosilver includes: Ag 8%, P2O5 42%, CaSO 45%, TeO2 10%, V2O5 34%, GeO2 0.6%, GaInSn 0.2%, and In 0.2%; the D50 particle size of the low-temperature glass powder is 300nm and the glass transition temperature is 218.5℃.
[0061] Example 5
[0062] This embodiment provides a low-temperature sintering silver paste with high sintering activity and a preparation method thereof, which is different from Embodiment 1 in that:
[0063] The low-temperature sintering silver paste includes 40 parts of micron silver powder, 0.5 parts of nano silver-coated low-temperature glass powder, 0.5 parts of bisphenol A epoxy resin, 0.1 parts of dicyandiamide, and 3 parts of diethylene glycol butyl ether.
[0064] In step S12 of the method for preparing the low-temperature sintering silver paste, 40 parts of micron silver powder, 0.5 parts of low-temperature glass powder, 0.5 parts of bisphenol A epoxy resin, 0.1 parts of dicyandiamide and 3 parts of diethylene glycol butyl ether are weighed.
[0065] Example 6
[0066] This embodiment provides a low-temperature sintering silver paste with high sintering activity and a preparation method thereof, which is different from Embodiment 1 in that:
[0067] The low-temperature sintering silver paste includes 95 parts of micron silver powder, 10 parts of nano silver-coated low-temperature glass powder, 10 parts of bisphenol A epoxy resin, 5 parts of dicyandiamide, and 50 parts of diethylene glycol butyl ether.
[0068] The method for preparing low-temperature sintering silver paste, in step S12, is to weigh 95 parts of micron silver powder, 10 parts of low-temperature glass powder, 10 parts of bisphenol A epoxy resin, 5 parts of dicyandiamide and 50 parts of diethylene glycol butyl ether.
[0069] Example 7
[0070] This embodiment provides a low-temperature sintering silver paste with high sintering activity and a preparation method thereof. The difference from Embodiment 1 is that the D50 particle size of the micron or submicron silver powder is 0.5 μm, and the D50 particle size of the low-temperature glass powder is 100 nm.
[0071] Example 8
[0072] This embodiment provides a low-temperature sintering silver paste with high sintering activity and a preparation method thereof. The difference from Embodiment 1 is that the D50 particle size of the micron or submicron silver powder is 10 μm, and the D50 particle size of the low-temperature glass powder is 500 nm.
[0073] Example 9
[0074] This embodiment provides a low-temperature sintering silver paste with high sintering activity and a preparation method thereof, which is different from Embodiment 1 in that:
[0075] The low-temperature sintering silver paste also includes 3 parts of nano-indium oxide.
[0076] The invention discloses a method for preparing a low-temperature sintering silver paste. In step S12, 70 parts of micron silver powder, 5 parts of nano-silver-coated low-temperature glass powder, 5 parts of bisphenol A epoxy resin, 2.5 parts of dicyandiamide, 25 parts of diethylene glycol butyl ether and 3 parts of nano-indium oxide powder are weighed; in step S14, the micron silver powder, nano-silver-coated low-temperature glass powder and nano-indium oxide powder are added to a dispersion liquid and mixed evenly, and then ground to obtain a low-temperature sintering silver paste.
[0077] Comparative Example 1
[0078] This comparative example provides a DD-1760 series silver paste.
[0079] Comparative Example 2
[0080] This comparative example provides a low-temperature sintering silver paste with high sintering activity and a preparation method thereof.
[0081] The low-temperature sintering silver paste comprises: 70 parts of micron silver powder, 5 parts of nano silver powder, 5 parts of bisphenol A epoxy resin, 2.5 parts of dicyandiamide, and 25 parts of diethylene glycol butyl ether; wherein the D50 particle size of the micron silver powder is 5 μm, and the D50 particle size of the nano silver powder is 95 nm.
[0082] The method for preparing low-temperature sintering silver paste comprises the following steps:
[0083] S1: Weigh 70 parts of micron silver powder, 5 parts of nano silver powder, 5 parts of bisphenol A epoxy resin, 2.5 parts of dicyandiamide and 25 parts of diethylene glycol butyl ether;
[0084] S2: dispersing bisphenol A epoxy resin and dicyandiamide in diethylene glycol butyl ether to obtain a dispersion;
[0085] S3: adding micron silver powder and nano silver powder into the dispersion and mixing them evenly, and then grinding them to obtain a low-temperature sintering silver paste.
[0086] Comparative Example 3
[0087] This comparative example provides a low-temperature sintering silver paste with high sintering activity and a preparation method thereof, which is different from Example 1 in that:
[0088] In the low-temperature sintering silver paste, ordinary glass powder is used to replace the nano-silver-coated low-temperature glass powder of the present application, wherein the ordinary glass powder includes 35 parts of TeO2, 15 parts of SiO2, 15 parts of PbO, 10 parts of B2O3, 20 parts of ZnO and 5 parts of Li2O.
[0089] Comparative Example 4
[0090] This comparative example provides a low-temperature sintering silver paste with high sintering activity and a preparation method thereof, which is different from Example 1 in that:
[0091] In the low-temperature sintering silver paste, the low-temperature glass powder coated with nanosilver does not contain GaInSn.
[0092] Comparative Example 5
[0093] This comparative example provides a low-temperature sintering silver paste with high sintering activity and a preparation method thereof, which is different from Example 1 in that:
[0094] In the low-temperature sintering silver paste, the low-temperature glass powder coated with nanosilver does not contain In.
[0095] Related performance test analysis:
[0096] 1. From Figure 1 It can be seen from the SEM image that after the low-temperature sintering silver paste provided in Example 1 of the present invention is sintered and solidified at low temperature to form a gate electrode, a corrosion zone exists at the interface of the silicon layer, and the corrosion degree exceeds 0.1 μm, which indicates that the low-temperature sintering silver paste provided in the embodiment of the present invention can penetrate the TCO layer of the solar cell and contact the silicon layer during low-temperature sintering, forming a contact layer at the interface ( Figure 1 The dotted box in the figure shows the cross section of the solar cell), thus significantly reducing the interlayer contact resistance and improving the conversion efficiency of the solar cell.
[0097] 2. The low-temperature sintered silver pastes provided in Examples 1 to 9 and Comparative Examples 1 to 5 were prepared into grid electrodes by screen printing and assembled into solar cells for testing of sintering temperature, volume resistivity, contact resistance and conversion efficiency (with Comparative Example 1 as a benchmark, the test values are the values increased or decreased relative to Comparative Example 1). The test results are shown in Table 1:
[0098] Table 1
[0099]
[0100] It can be seen from Table 1 above that the volume resistivity and contact resistance of the solar cells assembled with the grid electrodes prepared from the low-temperature sintered silver paste provided in Examples 1 to 9 are significantly lower than those in Comparative Examples 1 to 3; the conversion efficiency of the solar cells assembled with the grid electrodes prepared from the low-temperature sintered silver paste provided in Examples 1 to 9 is significantly higher than that in Comparative Examples 1 to 3, which is mainly due to the fact that the nanosilver in the nanosilver-coated low-temperature glass powder of the present application can promote the adhesion between micron or submicron silver powders to form a tightly bonded grid electrode, thereby reducing the volume and reducing the volume resistivity; the low-temperature glass powder in the nanosilver-coated low-temperature glass powder can penetrate the TCO layer at a low temperature, so that the nanosilver melted in the low-temperature glass powder regenerates nanosilver at the interface between the TCO layer and the silicon layer after solidification to form an ohmic contact with the silicon layer, thereby reducing the contact resistance in the heterojunction solar cell and improving the photoelectric conversion efficiency of the photovoltaic cell.
[0101] The volume resistivity and contact resistance of the solar cell assembled into the grid electrode prepared by the low-temperature sintering silver paste provided in Example 1 are significantly lower than those in Comparative Example 4, indicating that the Ga or In single metal in the low-temperature glass powder, as an ultra-low melting point element, reduces the melting temperature of the glass powder, allowing the glass powder to melt and flow at a lower temperature, which can not only promote the combination of micron or submicron silver powder, improve density, and reduce volume resistivity, but also penetrate the TCO layer, so that the nanosilver melted in the low-temperature glass powder can regenerate nanosilver at the interface between the TCO layer and the silicon layer after solidification, forming ohmic contact with the silicon layer, thereby reducing the contact resistance.
[0102] The volume resistivity and contact resistance of the solar cell assembled into the grid electrode prepared by the low-temperature sintering silver paste provided in Example 1 are significantly lower than those of Comparative Example 5, indicating that the GaInSn alloy in the low-temperature glass powder has an ultra-low melting point and, as a promoter, can make the glass powder melt and flow at a lower temperature, promote the combination of micron or submicron silver powder, thereby improving the density and reducing the volume resistivity, and can also co-melt with the TCO layer elements, so that the glass powder can infiltrate the TCO layer material and penetrate the TCO layer, so that the nanosilver melted in the low-temperature glass powder can regenerate nanosilver at the interface between the TCO layer and the silicon layer after solidification, forming ohmic contact with the silicon layer, thereby reducing the contact resistance.
[0103] The above description is only a preferred embodiment of the present application and is not intended to limit the present application. Any modifications, equivalent substitutions and improvements made within the spirit and principles of the present application should be included in the protection scope of the present application.
Claims
1. A low temperature sintering silver paste with high sintering activity, It is characterized in that The invention comprises the following components in parts by weight: 40-95 parts of micron or submicron silver powder, 0.5-10 parts of conductive low-temperature glass powder, 0.5-10 parts of resin, 0.1-5 parts of curing agent, 3-50 parts of solvent, and 0-10 parts of additive; Wherein, the conductive low-temperature glass powder is a low-temperature glass powder coated with nano-silver; the low-temperature glass powder coated with nano-silver is composed of Ag 1-10%, P 2 O 5 5~60%, CaSO 4 5~20%, TeO 2 10~50%, V 2 O 5 5~50%, GeO 2 0.2~10%, GaInSn0.2~5%, Ga or In 0.2~5%, the total weight is 100%; The glass transition temperature of the low temperature glass powder is 120-220°C.
2. The low temperature sintering silver paste according to claim 1, It is characterized in that The D50 particle size of the low-temperature glass powder is 100-500 nm; And / or, the D50 particle size of the nano-silver coated low-temperature glass powder is 150-600 nm.
3. The low temperature sintering silver paste according to claim 1 or 2, It is characterized in that The D50 particle size of the micron or submicron silver powder is 0.5-10 μm.
4. The low temperature sintering silver paste according to claim 1 or 2, It is characterized in that The micron or submicron silver powder includes any one of polyvinyl pyrrolidone-modified micron or submicron silver powder and oleic acid-modified micron or submicron silver powder.
5. The low temperature sintering silver paste according to claim 1 or 2, It is characterized in that The resin is selected from at least one of epoxy resin, polyester resin, acrylic resin, ethyl cellulose and polyvinyl butyral; The curing agent is selected from at least one of dicyandiamide, hexafluoroantimonate, methyltetrahydrophthalic anhydride, dodecenylsuccinic anhydride, polysebacic anhydride, and boron trinitride ethylamine complex; The solvent is selected from at least one of diethylene glycol butyl ether, diethylene glycol ethyl ether, diethylene glycol diethyl ether, diethylene glycol dibutyl ether, ethylene glycol phenyl ether, diethylene glycol ethyl ether acetate, diethylene glycol butyl ether acetate, DBE, dodecanol ester, hexadecanol ester, terpineol, propylene glycol methyl ether acetate, 1-phenoxy-2-propanol, and diacetin.
6. A method for preparing a low-temperature sintering silver paste with high sintering activity according to any one of claims 1 to 5, It is characterized in that The following steps are involved: Weigh micron or submicron silver powder, conductive low-temperature glass powder, resin, curing agent, solvent and additives; Dispersing the resin and the curing agent in the solvent to obtain a dispersion; The micron or submicron silver powder, the conductive low-temperature glass powder and the additive are added into the dispersion and mixed evenly to obtain a low-temperature sintering silver paste.
7. The preparation method according to claim 6, It is characterized in that The steps of preparing the conductive low-temperature glass powder include: dissolving a silver source in a solvent, then adding low-temperature glass powder and a reducing agent, performing liquid phase reduction treatment, growing nanosilver on the surface of the low-temperature glass powder, and then filtering, washing and drying in sequence to obtain the conductive low-temperature glass powder.
8. The preparation method according to claim 7, It is characterized in that The steps of preparing the low temperature glass powder include: Weigh P 2 O 5 Powder, CaSO 4 Powder, TeO 2 Pink, V 2 O 5 Powder, GeO 2 Powder, GaInSn alloy liquid, Ga or In single substance; The P 2 O 5 Powder, CaSO 4 Powder, TeO 2 Pink, V 2 O 5 Powder and GeO 2 The powders are mixed and then subjected to a first smelting treatment, and then quenched to obtain a first glass slag; The first glass slag, GaInSn alloy liquid, and Ga or In single substance are subjected to a second smelting treatment under a protective atmosphere to obtain a second glass slag; The second glass slag is sand-milled and then sieved to obtain a low-temperature glass powder with a D50 particle size of 100-500 nm.
9. The preparation method according to claim 8, It is characterized in that The temperature of the first smelting treatment is 700-1500° C. and the time is 10-120 min; And / or, the temperature of the second smelting treatment is 200-300° C., and the time is 10-120 min.
